Review of Climate-Resilient Agriculture for Ensuring Food Security: Sustainability Opportunities and Challenges of India - Sahoo, Satiprasad; Singha, Chiranjit; Govind, Ajit; Moghimi, Armin (Elsevier, 2025)
Climate Resilient Agriculture (CRA) effectively responds to climate change while contributing to sustainable productivity adapted to local hydro-meteorological conditions. CRA provides resilience to climate variability by enhancing agricultural viability through water exchange between surface and groundwater systems. In water stressed countries such as India, where demand for water from agriculture, industry, and domestic use is increasing, CRA offers ways to address current and future food security challenges. This review examines the role of the CRA in agricultural sustainability and community participation in India. It assesses critical CRA projects and policies in India and explores how CRA can improve water policy by integrating farmers’ perspectives in groundwater-based agriculture. The study also shows that collaboration between government agencies, NGOs, and local groups is important to sustaining CRA initiatives. Discussions indicated that empirical studies, clear sustainability indicators, and integration of advanced technology such as artificial intelligence and geo-spatial tools are needed to improve India’s adaptation strategies to climate change. This study highlighted how CRA aligns with key SDGs by addressing poverty, hunger, climate action, and community wellbeing. GRACE data indicated that northwestern India emerged as a critical water scarcity hotspot, displaying negative trends of around − 7.413 cm per year. Furthermore, the analysis clearly showed that the Western Dry Region, Western Himalayan, and Gangetic Plain agro-ecological zone (AEZ) experienced the sharpest declines in equivalent water thickness (EWT) compared to other AEZ regions in India. The review also highlighted the value of knowledge sharing platforms and tailored CRA strategies that increase agricultural productivity and enable farmers to make informed decisions in the face of climate uncertainty.